1993
DOI: 10.1159/000116976
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Trismus Caused by Vertebrobasilar Dolichoectasia

Abstract: Vertebrobasilar dolichoectasia is a relatively uncommon pathological entity and generally asymptomatic. We report a quite unusual case of unilateral motor trigeminal involvement with trismus, due to VD. Apart from tetanus or local morbid conditions of the mouth, trismus is often attributed to disturbed programming and co-ordination of the masticatory muscles within the mesencephalic nucleus. The possibility of truncal compression of the trigeminal motor root by vertebrobasilar dolichoectasia being responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…No inciting events nor prior imaging findings on further review explained this development. Marchiafava-Bignami disease and basilar artery thrombosis have been rare imaging findings described in association with development of trismus in context of CPM [6,7], as well as vertebrobasilar dolichoectasia [8], though neither conditions were apparent on head CT or brain MRI of this patient. She had no documented history of seizures or head injuries.…”
Section: Disclosure Statementmentioning
confidence: 58%
“…No inciting events nor prior imaging findings on further review explained this development. Marchiafava-Bignami disease and basilar artery thrombosis have been rare imaging findings described in association with development of trismus in context of CPM [6,7], as well as vertebrobasilar dolichoectasia [8], though neither conditions were apparent on head CT or brain MRI of this patient. She had no documented history of seizures or head injuries.…”
Section: Disclosure Statementmentioning
confidence: 58%
“…Our patient had bilaterally cortical-subcortical lesions near the operculum and insula, disconnecting those areas from the supplementary motor area, premotor and precentral sensorimotor cortical areas, disrupting the highest-level voluntary motor command of the jaw for voluntary jaw opening and closing, but preserving pontine automatic brainstem reflexes despite a previous unilateral brainstem lesion. This is a unique situation that interestingly demonstrates that a unilateral pontine lesion, in the presence of biopercular suprasegmental lesions, is not sufficient to make the reflex jaw movement disappear, but may require bilateral pontine lesions, probably because of a bilateral representation of intersegmental brachial reticular reflexes [5,19].…”
Section: Discussionmentioning
confidence: 93%
“…Known causes of trismus have included mechanical etiologies (e.g., exostoses of the coronoid process), inflammatory disease (e.g., rheumatoid arthritis or osteomyelitis), infection (e.g., actinomycosis or tetanus), fibrosis (i.e., post‐surgical or post‐radiation changes), neoplasm, and disorders affecting the peripheral nervous system (e.g. Trotter's syndrome) or central nervous system (e.g., vertebrobasilar dolichoectasia) 1,7–11 . A previous cross‐sectional study has shown that 24% of patients with head and neck cancer experience trismus 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Trotter's syndrome) or central nervous system (e.g., vertebrobasilar dolichoectasia). 1,[7][8][9][10][11] A previous cross-sectional study has shown that 24% of patients with head and neck cancer experience trismus. 12 The various treatments for trismus can be categorized into conservative medical treatment, physical therapy, and surgery.…”
Section: Introductionmentioning
confidence: 99%